2016
DOI: 10.1080/10401334.2016.1164049
|View full text |Cite
|
Sign up to set email alerts
|

Social Workers as Workplace-Based Instructors of Alcohol and Drug Screening, Brief Intervention, and Referral to Treatment (SBIRT) for Emergency Medicine Residents

Abstract: Social work colleagues can be effective in teaching SBIRT to residents in the workplace, and our residents highly valued learning from social workers, who all had prior training in motivational interviewing. In the implementation of this curriculum, the clinical demands of residents must be taken into account when teaching occurs, and having multiple social worker instructors was instrumental.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Similar to prior years, the most common study populations were medical students (21/75; 28%) and residents (48/75; 64%) . Interestingly, this year only one study addressing medical students was highlighted for excellence, in contrast to prior years.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Similar to prior years, the most common study populations were medical students (21/75; 28%) and residents (48/75; 64%) . Interestingly, this year only one study addressing medical students was highlighted for excellence, in contrast to prior years.…”
Section: Discussionmentioning
confidence: 92%
“…As the field of medical education continues to grow, we expect that this trend will continue. There was a decrease in the number of funded studies in 2016; 11% of all articles compared to 20% in 2015 and 16% in 2014. There is some literature to suggest that funded medical education research may be of higher quality .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…As a result of the need for IPE, a number of investigative educators have developed and studied interprofessional training for students to better prepare them for the workforce (Duong, O'Sullivan, Satre, Soskin, & Satterfield, 2016;Monteiro et al, 2017;Neander et al, 2018;Neft, 2018;Peterson, 2017). Collectively, these programs have demonstrated that interprofessional trainings have high satisfaction among students and enhance interprofessional competence, condition specific knowledge, skill, and attitudes around SBIRT and working with patients with substance use disorders.…”
Section: Ipe Literaturementioning
confidence: 99%